Faktor – Faktor yang Mempengaruhi Kinerja Karyawan pada PT Lima Prima Jaya Kota Solok - Esi Sriyanti; Rasidah Nasrah; Okti Wulandari (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this research is to identify: (1) the effect of the Work Environment on Employee Performance at PT Lima Prima Jaya in Solok City, (2) the effect of Individual Characteristics on Employee Performance at PT Lima Prima Jaya in Solok City, and (3) the combined effect of Work Environment and Individual Characteristics on Employee Performance at PT Lima Prima Jaya in Solok City. For this study, a total sampling method was employed, resulting in 30 respondents. The study utilizes a quantitative approach with primary data. The findings indicate that: (1) the X1 variable, which represents the Work Environment, has a t value exceeding the t-table (4.291 > 2.05183) and a significance level of 0.000 < 0.05, suggesting that the work environment has a partial impact on employee performance; (2) the X2 variable, which represents Individual Characteristics, has a t value less than the t-table (1.743 < 2.05183) and a significance level of 0.093 > 0.05, indicating that individual characteristics do not have a partial impact on employee performance; (3) the results of the F-test reveal that the F-count is greater than the F-table (13.519 > 3.354), indicating that the work environment and individual characteristics together influence employee performance. This is further supported by an R Square value of 0.500, which indicates that the work environment and individual characteristics account for 50.0% of employee performance at PT Lima Prima Jaya in Solok City, with the remaining 50.0% being affected by other factors not covered in this research.